Qué es la Geografía? : Breve introducción al estudio y métodos de la ciencia geográfica (Ediciones UCC, 2018)
What is geography? What do geographers do? It is a fact that there is a fairly widespread lack of knowledge about the object of study of geography, a discipline that studies the characteristics of the environment in relation to society. The purpose of this book is to help students who are beginning in geography to understand the basic questions of this science, to make known the main methods that it uses and to guide them on study techniques and scientific work at the university so that they can achieve successful learning. The added value of this text is not to expose new scientific knowledge, but to develop in an understandable and simple way the topics that occupy the knowledge and thinking of the geographer and contribute to a better understanding of a key subject in the development of harmonious societies.